Salt-assisted synthesis of defect-rich transition metal M-NC porous nanosheet materials and preparation methods and applications thereof
Through salt-assisted synthesis of defect-rich transition metal M-NC porous nanosheet materials, the existing catalysts are solved, and the existing catalysts are easily oxidized, and efficient and low-cost CO2 reduction catalyst preparation is achieved, which improves catalytic performance and industrial application potential.
Patent Information
- Application Number
- CN202310584612.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-23
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-05-23
AI Technical Summary
The existing electrocatalytic CO2 reduction catalysts have defects such as high raw material prices and easy oxidation of catalysts, making it difficult to achieve industrial application.
The defect-rich transition metal M-NC porous nanosheet material is used to assist in the synthesis of defect-rich transition metal M-NC porous nanosheet materials. The reaction of the phthalocyanine transition metal precursor with a mixed salt system of glucose, urea and sodium chloride-potassium chloride is carried out in an argon atmosphere to form a catalyst with a high specific surface area and defect-rich catalyst.
The selectivity and activity of CO2 reduction to CO2 is significantly improved, the preparation process is simplified, the production cost is reduced, and the large-scale production of catalysts and the stability of chemical properties is achieved.
Smart Images

Figure CN116623193B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to electrocatalytic reduction of CO 2 The field of materials, specifically relates to salt-assisted synthesis of defect-rich transition metal M-NC porous nanosheet materials and their preparation methods and applications. Background Art
[0002] Due to the continuous development and changes of society, the concentration of carbon dioxide in the atmosphere is increasing day by day, bringing about a series of environmental problems such as the greenhouse effect. Therefore, people need to seek solutions to improve the current situation. 2 , people have developed strategies such as photocatalysis, electrocatalysis, and thermal catalysis to treat CO 2 However, photocatalysis has problems such as low efficiency and low selectivity, and thermal catalysis has problems such as harsh reaction conditions. Therefore, electrocatalysis with controllable operating conditions and driven by clean energy can effectively alleviate the environmental pressure caused by large amounts of carbon dioxide emissions.
[0003] Electrocatalytic carbon dioxide is the process of using electrical energy to control operating conditions and electrochemical parameters to react with CO on a catalyst. 2 Through a series of adsorption, activation, electron transfer, desorption and other processes, the products can be carbon monoxide, methane, formic acid, ethylene and a series of high value-added multi-carbon products, so it can reduce the CO in the atmosphere. 2 While reducing the content, it also utilizes its resources and brings economic benefits. 2 The energy required is high, and it is necessary to overcome the breaking of the C=O bond, so the construction of the catalyst system has become a major step in the electrocatalytic CO 2 The core issues that need to be addressed in this field.
[0004] For CO 2 The electrode materials used are different for different reduction products. 2 When reduced to CO, precious metals such as Au and Ag are often used as electrode material substrates.
[0005] The Chinese patent with patent number CN111672505A discloses the use of in-situ reduction of silver oxide precursor to convert it into nano silver particles, which then provides a large number of grain boundaries to form low coordination number sites for CO 2 Reduction provides active sites, and the preparation of this electrode material can provide higher selectivity. However, the prepared catalyst has defects such as high raw material prices and easy oxidation of the catalyst, which makes it difficult to achieve industrial application. Therefore, people need to seek to develop catalysts with low prices, large-scale production, simplified production processes, and stable chemical properties.
[0006] Carbon-based materials, as a low-cost material with good electrical conductivity and stable chemical properties, have been widely developed and applied in the field of materials.
[0007] Two-dimensional nanomaterials have unique physical and chemical properties due to their high specific surface area and a large number of distributed active sites. Designing and developing a carbon-based two-dimensional nanomaterial can combine the advantages of both, optimize catalyst preparation, and be beneficial to achieving mass production.
[0008] The common strategies for preparing two-dimensional nanomaterials have the disadvantages of complex preparation process, low yield and difficulty in industrialization. Therefore, it is of research significance to develop a solution to overcome the above shortcomings. Summary of the invention
[0009] The present invention provides a method for preparing a salt-assisted synthesis of defect-rich transition metal M-NC porous nanosheet material. The preparation method is simple and efficient, and the method can be used to prepare a nitrogen-doped carbon porous nanosheet with defect-rich transition metal sites. The porous nanosheet can significantly provide electrocatalytic reduction of CO 2 The selectivity and activity of CO.
[0010] A specific embodiment of the present invention provides a method for preparing a salt-assisted synthesis defect-rich transition metal M-NC porous nanosheet material, comprising:
[0011] (1) adding glucose and urea to an ethanol-water mixed solution of a phthalocyanine transition metal precursor, stirring to obtain a mixed solution, adding a sodium chloride-potassium chloride mixed salt system to the mixed solution, stirring to obtain a mixed sample after drying and grinding;
[0012] (2) calcining the mixed sample in an argon atmosphere by a gradient temperature increase, and obtaining a defect-rich transition metal nitrogen-doped carbon porous nanosheet material containing a sodium chloride-potassium chloride mixed salt system after natural cooling;
[0013] (3) The defect-rich transition metal nitrogen-doped carbon porous nanosheet material obtained in step (2) is sequentially acid-washed, water-washed and alcohol-washed, and then vacuum-dried to obtain a salt-assisted synthesis defect-rich transition metal M-NC porous nanosheet material.
[0014] The preparation method of the present invention utilizes the unique MN of phthalocyanine macrocyclic compounds 4The structure can significantly increase the number of active sites in the final catalyst product, and at the same time, a molten salt environment is used to synthesize porous two-dimensional nanosheets with a large surface area, thereby increasing the number of active site exposures. During the preparation process, the molten salt has an etching effect, which can produce a large number of defects on the carbon-based material, that is, forming rich defects. The defects can jointly regulate the electrocatalysis with the metal active sites, thereby improving the electrocatalytic performance of the salt-assisted synthesis of defect-rich transition metal M-NC porous nanosheet materials.
[0015] In step (1):
[0016] Furthermore, in the ethanol-water mixed solution of the phthalocyanine transition metal precursor, the concentration of the phthalocyanine transition metal precursor is 0.25-0.5 g / L, wherein the phthalocyanine transition metal precursor is iron phthalocyanine, nickel phthalocyanine or cobalt phthalocyanine.
[0017] If the concentration of the phthalocyanine transition metal precursor is low, the active sites of the salt-assisted synthesis of defect-rich transition metal M-NC porous nanosheet materials obtained are low, and the catalytic effect is poor; if the concentration of the phthalocyanine transition metal precursor is high, the active sites of the salt-assisted synthesis of defect-rich transition metal M-NC porous nanosheet materials obtained are too many, which affects the CO 2 Gas adsorption and diffusion process. Therefore, the appropriate concentration of phthalocyanine transition metal precursors can provide suitable active sites and achieve better catalytic performance.
[0018] Furthermore, in the ethanol-water mixed solution of the phthalocyanine transition metal precursor, the volume ratio of ethanol to water is 1:1-5:1.
[0019] Since the phthalocyanine transition metal precursor has poor dispersibility in pure water, it is very easy to agglomerate and cannot be fully mixed with other raw materials. The present invention provides a suitable ratio of ethanol and aqueous solution, so that the phthalocyanine transition metal precursor can be evenly dispersed and fully mixed with the carbon source, nitrogen source and mixed salt.
[0020] Further, phthalocyanine transition metal precursors were added to the ethanol-water solution and stirred to dissolve, and then glucose and urea were added and stirred for 0.5 h, and then mixed salt was added and stirred for 0.5 h. This step is also to allow the raw material precursors to be fully mixed so that they can be evenly dispersed in the subsequent molten salt environment.
[0021] Furthermore, the mass ratio of glucose to urea is 1:1-2:1, and the concentration of glucose and urea in the mixed solution is 10-15 g / L.
[0022] Glucose is used as the carbon source and urea as the nitrogen source. Although phthalocyanines already contain nitrogen, urea can provide a large amount of nitrogen, thereby better doping nitrogen on carbon-based nanosheets. Among them, too high a nitrogen source concentration will lead to excessive element doping, too high a nitrogen density, and too low a nitrogen source concentration will not play a doping role.
[0023] Furthermore, the mass ratio of the sodium chloride-potassium chloride mixed salt system to the phthalocyanine transition metal precursor is 5: 1-20: 1. Too high a mass ratio will cause salt waste, and too low a mass ratio will result in failure to provide a sufficient mixed salt environment.
[0024] Furthermore, in the sodium chloride-potassium chloride mixed salt system, the molar ratio of sodium chloride to potassium chloride is 1: 1-3: 1. If the molar ratio of the mixed salt is too high or too low, the desired melting point environment cannot be achieved.
[0025] Since the melting point of pure sodium chloride is 801°C and the melting point of pure potassium chloride is 770°C, a single pure salt environment requires a higher melting point to provide a melting environment. Then, too high a temperature will cause excessive graphitization of the carbon source, affecting the catalytic performance. Therefore, a eutectic mixed salt system is needed to lower its melting point.
[0026] More preferably, the eutectic point of a mixed salt system of sodium chloride and potassium chloride in a molar ratio of 1:1 is 658° C. A lower melting temperature can avoid excessive graphitization of the carbon base.
[0027] In step (2):
[0028] Furthermore, the purity of the argon gas is 95%-99.999%, and the gas flow rate of the argon gas is 15-20 mL / min. As an inert gas, argon gas can isolate the air and protect the material from reacting with the air during the calcination process, and also play a role in ensuring the safety of the experiment. Therefore, high-purity argon gas is of great significance for experimental preparation.
[0029] Furthermore, the mixed sample is calcined by a gradient temperature increase method, and the calcination parameters are: heating to 700-1100°C at a heating rate of 3-5°C / min, and then keeping the temperature for 0.5-4h.
[0030] The calcination temperature provided by the present invention is higher than the calcination temperature of the eutectic point of the mixed salt system, which can form a molten salt environment. After reaching the eutectic point, the non-solvated ions therein have a strong template effect, and the material can be quickly formed and the catalyst product can be stabilized by a strong polarization effect. On the other hand, the molten salt environment plays a role of liquid sealing, ensuring that at a high flow rate of argon gas, the two-dimensional nanomaterial can be effectively protected from being carried away by the airflow after synthesis, thereby increasing the yield of the catalyst. If there is no molten salt to act as a cap, the catalyst is very easy to drift, resulting in a decrease in yield.
[0031] At the same time, the chemical properties of molten salt are stable. The product can be formed in a relatively mild and stable environment within the range of 700-1100°C. The insulation time affects the anchoring effect of the metal active sites. Too short insulation time makes it impossible for the metal sites to be fully anchored on the carbon-based material.
[0032] The appropriate holding time allows the precursors to fully contact and nitrogen to be successfully doped on the carbon-based nanosheets. 4 The sites are fully anchored on the base material in large quantities. During the natural cooling process, the molten salt gradually solidifies and plays a certain role in forming pores on the carbon-based nanosheets.
[0033] In step (3):
[0034] Furthermore, the defect-rich transition metal nitrogen-doped carbon porous nanosheet material obtained in step (2) is sequentially pickled, and the pickling process is: the acid used is hydrochloric acid, nitric acid, sulfuric acid, etc., and the concentration of the acid used is 0.5-2 mol / L. The defect-rich transition metal nitrogen-doped carbon porous nanosheet material obtained by washing with an acid of a suitable concentration can wash away the agglomerated metal that may be formed during the calcination process. After the pickling, it is further washed with water and alcohol to remove the mixed salt, and the defect-rich transition metal M-NC porous nanosheet material synthesized by salt assistance is simply obtained.
[0035] Furthermore, the vacuum drying process is as follows: the vacuum drying temperature is 60-80°C and the time is 8-24h.
[0036] The present invention also provides a salt-assisted synthesis defect-rich transition metal M-NC porous nanosheet material prepared by the method for preparing the salt-assisted synthesis defect-rich transition metal M-NC porous nanosheet material.
[0037] The present invention also provides the salt-assisted synthesis of defect-rich transition metal M-NC porous nanosheet material as an electrode catalyst in electrocatalysis of CO 2 Application in.
[0038] Furthermore, the electrode carrier of the catalyst is carbon paper, carbon cloth, etc. Carbon paper has good conductivity and support, and does not participate in the electrocatalytic reaction.
[0039] Furthermore, the salt-assisted synthesis of defect-rich transition metal nitrogen-doped carbon porous nanosheets was used as a catalyst and uniformly dispersed in a perfluorosulfonic acid resin Nafion solution and placed on a carbon paper support as a working electrode. Together with the Ag / AgCl reference electrode and the platinum column counter electrode, a three-electrode system was formed to electrocatalyze CO 2 reduction.
[0040] Furthermore, the catalyst loading concentration is 1-4 mg / cm 2At the same time, the concentration of the perfluorosulfonic acid resin Nafion solution is 2-10%wt. This ratio ensures good adhesion of the catalyst on the carbon paper support and guarantees its catalytic performance.
[0041] The catalyst material prepared by the present invention is loaded on carbon paper as an electrode, an electrocatalytic experiment is carried out in an H-type electrolytic cell, an electrochemical workstation is used to test the electrochemical performance, and a gas chromatograph is used to detect the product.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] (1) Using MN 4 Phthalocyanine metal precursors with a structure are more likely to form MN than metal salt precursors. 4 structure. At the same time, for the heating process, MN 4 It can be directly anchored to the carbon-based carrier in one step, which simplifies the heating process and reduces energy loss. The preparation method is simple, efficient and highly controllable.
[0044] The sodium chloride-potassium chloride eutectic mixed salt system greatly reduces the eutectic point of the salt. At the same time, the mixed salt system can act as a liquid seal in the molten state to prevent the loss of raw materials caused by the pyrolysis of the material and the escape of the product nanosheets. After the mixed salt system reaches the eutectic point, the precursor transfers mass faster in the higher temperature molten salt environment, accelerating the formation of the product. The non-solvated ions in the molten salt have a strong template effect, which can inhibit the sp-bonding of carbon materials through strong polarization. 2 The vertical growth of the connection makes the carbon-based material grow into an extremely thin nanosheet form. During the natural cooling process, the salt can act as a pore-forming agent. The above effects increase the specific surface area of the material and strengthen the CO 2 The mass transfer provided more possibilities for active site loading and optimized the performance of the catalyst.
[0045] During the material preparation and calcination process, the presence of high-energy ions in the molten salt system plays an etching role, thereby generating a large number of defects on the carbon-based materials. The defects and metal sites jointly regulate electrocatalysis, thereby improving the electrocatalytic performance.
[0046] In the process of removing mixed salts, since the sodium chloride-potassium chloride mixed salt system is easily soluble in water, it can be removed by simple water washing. The operation process is simple and the cost is low.
[0047] (2) The present invention provides a suitable concentration of the phthalocyanine transition metal precursor in the ethanol-water mixed solution of the phthalocyanine transition metal precursor, so that the final salt-assisted synthesis of defect-rich transition metal M-NC porous nanosheet material has a more appropriate amount of active sites, achieving better catalytic performance.
[0048] (3) The present invention provides an appropriate ratio of ethanol and aqueous solution, so that the phthalocyanine transition metal precursor can be evenly dispersed and fully mixed with the carbon source, nitrogen source, and mixed salt.
[0049] (4) The optimal ratio is obtained by optimizing the molar ratio of the mixed salt, which is beneficial to the formation of nitrogen-doped carbon-based nanosheets and the loading of metal sites, so that the obtained defect-rich transition metal M-NC porous nanosheet material has better catalytic performance.
[0050] (5) The calcination temperature provided by the present invention is higher than the calcination temperature of the eutectic point of the mixed salt system, which can form a molten salt environment. After reaching the eutectic point, the non-solvated ions therein have a strong template effect, which can enable the material to quickly form and stabilize the catalyst product through a strong polarization effect. On the other hand, the molten salt environment plays a role of liquid sealing, ensuring that at a high flow rate of argon gas, the two-dimensional nanomaterial can be effectively protected from being carried away by the airflow after synthesis, thereby increasing the yield of the catalyst. If there is no molten salt to act as a cap, the catalyst is very easy to drift away, resulting in a decrease in yield.
[0051] At the same time, the chemical properties of molten salt are stable. The product can be formed in a relatively mild and stable environment within the range of 700-1100°C. The insulation time affects the anchoring effect of the metal active sites. Too short insulation time makes it impossible for the metal sites to be fully anchored on the carbon-based material.
[0052] The appropriate holding time allows the precursors to fully contact and nitrogen to be successfully doped on the carbon-based nanosheets. 4 The sites are fully anchored on the base material in large quantities. During the natural cooling process, the molten salt gradually solidifies and plays a certain role in forming pores on the carbon-based nanosheets. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 This is a scanning electron microscope (SEM) image of the salt-assisted synthesis of defect-rich transition metal nitrogen-doped carbon porous nanosheet material prepared in Example 1;
[0054] Figure 2 The X-ray diffraction (XRD) pattern of the salt-assisted synthesis defect-rich transition metal nitrogen-doped carbon porous nanosheet material prepared in Example 1;
[0055] Figure 3 The specific surface area (BET) diagram of the salt-assisted synthesis defect-rich transition metal nitrogen-doped carbon porous nanosheet material prepared in Example 1;
[0056] Figure 4 The Raman spectra (Raman) of the salt-assisted synthesis defect-rich transition metal-doped porous nanosheet materials prepared in Example 1 and Comparative Example 1;
[0057] Figure 5 The current density diagram of the salt-assisted synthesis defect-rich transition metal-doped porous nanosheet material prepared in Example 1 and Comparative Example 1 at different potentials in an H-type cell;
[0058] Figure 6 This is a diagram of the Faraday efficiency (FE) of the salt-assisted synthesis defect-rich transition metal nitrogen-doped carbon porous nanosheet materials prepared in Example 1 and Comparative Example 1 at different potentials in an H-type cell. DETAILED DESCRIPTION
[0059] The present invention will be further described below in conjunction with the accompanying drawings and specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0060] Example 1
[0061] Weigh 0.015g of iron phthalocyanine FePc on an electronic balance and put it into a beaker. Use a measuring cylinder to measure 20ml of deionized water and 20ml of ethanol. Transfer the deionized water and ethanol to the beaker and stir magnetically for 0.5h to fully mix and dissolve the substances in the beaker. Then weigh 0.5g of glucose and 0.5g of urea on an electronic balance and add them to the beaker. Continue to stir magnetically for 0.5h to fully dissolve them. After stirring, weigh 4.4645g of sodium chloride and 5.6855g of potassium chloride on an electronic balance and add them to the solution and continue to stir until saturated.
[0062] The mixture was heated in an oil bath at 80°C with continuous stirring until most of the water in the mixture was evaporated, and the container was transferred to an oven at 60°C for drying overnight.
[0063] The dried mixture was quickly ground with an agate mortar, and the evenly ground mixture was transferred to a clean corundum boat. The corundum boat was placed in a tube furnace, and high-purity argon gas with a concentration of 99.999% was introduced, and the temperature was increased from room temperature to 1000°C at a heating rate of 5°C / min, and the temperature was kept at 1000°C for 3 hours, and then naturally cooled to room temperature.
[0064] The calcined product was transferred from the corundum boat to a clean beaker, and deionized water was added to the beaker and stirred for 4 hours to fully dissolve the mixed salt. The mixed solution was filtered and acid-washed with 1M hydrochloric acid solution for multiple times, then washed with deionized water for multiple times to neutralize, and finally washed with ethanol for multiple times to filter. The product after filtration was vacuum dried at 60°C for 12 hours to obtain the final salt-assisted synthesis of defect-rich transition metal nitrogen-doped carbon porous nanosheet material as Fe-NC-1000.
[0065] Application Example 1
[0066] The Fe-NC-1000 material in Example 1 was made into an electrode material for electrocatalytic CO 2 Cathode materials for CO production.
[0067] Weigh 0.01 g of Fe-NC-1000 catalyst on an analytical balance and place it in a 4 ml sample bottle, and use a pipette to take 900 μL of ethanol and 100 μL of 0.5% wt Nafion solution into the sample bottle. Ultrasonicate the mixture for 1 to 2 hours, and then stir it magnetically for 5 to 6 hours.
[0068] Cut the clean carbon paper into 1×3cm 2 Size, use non-conductive glue to paste, leaving 1×1cm 2 A blank area of 100 μL of the catalyst was evenly applied on the area in four drops. After each drop application, the area was dried under an infrared lamp for about 30 seconds.
[0069] In the H-type cell, equal amounts of 0.5 M potassium bicarbonate solution were added to the anode and cathode chambers as electrolytes. A platinum column electrode was used as the counter electrode and an Ag / AgCl electrode was used as the reference electrode. The electrochemical performance and selectivity were measured at different potentials.
[0070] Example 2
[0071] The preparation scheme is the same as that of Example 1, except that the calcination temperature in Example 1 is 800° C., and the final material is written as Fe-NC-800.
[0072] Application Example 2
[0073] The steps and methods are the same as those in Application Example 1, except that the Fe-NC-800 material prepared in Example 2 is used as the cathode catalyst material.
[0074] Comparative Example 1
[0075] Weigh 0.015g of iron phthalocyanine FePc on an electronic balance and put it into a beaker. Use a measuring cylinder to measure 20ml of deionized water and 20ml of ethanol. Transfer the deionized water and ethanol to the beaker and stir them magnetically for 0.5h to fully mix and dissolve the substances in the beaker. Then weigh 0.5g of glucose and 0.5g of urea on an electronic balance and add them to the beaker. Continue stirring magnetically for 0.5h to fully dissolve them.
[0076] The mixture was heated in an oil bath at 80°C with continuous stirring until most of the water in the mixture was evaporated, and the container was transferred to an oven at 60°C for drying overnight.
[0077] The dried mixture was quickly ground with an agate mortar, and the evenly ground mixture was transferred to a clean corundum boat. The corundum boat was placed in a tube furnace, and high-purity argon gas with a concentration of 99.999% was introduced, and the temperature was increased from room temperature to 1000°C at a heating rate of 5°C / min, and the temperature was kept at 1000°C for 3 hours, and then naturally cooled to room temperature.
[0078] The calcined product was transferred from the corundum boat to a clean beaker, and deionized water was added to the beaker and stirred for 4 hours to fully dissolve the mixed salt. The mixed solution was filtered and washed with 1M hydrochloric acid solution for several times, then washed with deionized water for several times to neutralize, and finally washed with ethanol for several times to filter. The product after filtration was vacuum dried at 60°C for 12 hours to obtain the final transition metal nitrogen-doped carbon porous nanosheet material, written as Fe-NC-saltfree-1000.
[0079] like Figure 5 As shown, the current density of the Fe-NC-saltfree-1000 material prepared in Comparative Example 1 at the same potential is much smaller than that of the Fe-NC-1000 material prepared in Example 1, so the Fe-NC-1000 material prepared in Example 1 has better catalytic activity.
[0080] like Figure 6 As shown, the selectivity of the Fe-NC-saltfree-1000 material prepared in Comparative Example 1 is much lower than that of the Fe-NC-1000 material prepared in Example 1 at the same potential. Therefore, the Fe-NC-1000 material prepared in Example 1 has higher selectivity.
[0081] Performance Analysis:
[0082] like Figure 1 As shown, the Fe-NC-1000 material prepared in Example 1 is in the form of nanosheets and is relatively thin.
[0083] like Figure 2 As shown, the Fe-NC-1000 materials prepared in Example 1 and Example 2 do not contain metal agglomeration and have a low degree of crystallization.
[0084] like Figure 3 As shown in Figure 1, the Fe-NC-1000 material prepared in Example 1 has a large specific surface area of 435.2231 m 2 / g, and there is a porous structure, which is CO 2 It provides good conditions for mass transfer.
[0085] like Figure 4 As shown, the Fe-NC-1000 material prepared in Example 1 produces a defect-rich feature under the etching action of salt.D / I G The ratio is 1.2417, which is significantly higher than the catalytic material prepared in Comparative Example 1.
[0086] like Figure 5 As shown, the catalyst materials prepared in Example 1 and Example 2 have good performance, wherein the current density of Example 1 at -1 (Vvs.RHE) reaches 48 mA cm -1 , greater than Comparative Example 1.
[0087] like Figure 6 As shown, the catalyst material prepared in Example 1 has high selectivity, and has the highest selectivity of 98% at a voltage of -0.5 V (vs. RHE).
[0088] In addition, it should be noted that the above-mentioned invention description content is intended to illustrate the scheme and application results of the present invention, and is not used to limit the present invention. Modifications made by technical personnel in this field within the core scope of the present invention are all within the scope defined by the claims attached to this application and are protected by the present invention.
Claims
1. A method for preparing a salt-assisted synthesis of defect-rich transition metal M-NC porous nanosheet material, characterized in that: include: (1) adding glucose and urea to an ethanol-water mixed solution of a phthalocyanine transition metal precursor, stirring to obtain a mixed solution, adding a sodium chloride-potassium chloride mixed salt system to the mixed solution, stirring to obtain a mixed sample after drying and grinding; (2) calcining the mixed sample in an argon atmosphere by a gradient temperature increase, and obtaining a defect-rich transition metal nitrogen-doped carbon porous nanosheet material containing a sodium chloride-potassium chloride mixed salt system after natural cooling; (3) sequentially acid-washing, water-washing and alcohol-washing the defect-rich transition metal nitrogen-doped carbon porous nanosheet material obtained in step (2) and then vacuum drying to obtain a salt-assisted synthesis defect-rich transition metal M-NC porous nanosheet material; In the ethanol-water mixed solution of the phthalocyanine transition metal precursor, the concentration of the phthalocyanine transition metal precursor is 0.25-0.5 g / L, wherein the phthalocyanine transition metal precursor is iron phthalocyanine, nickel phthalocyanine or cobalt phthalocyanine; The mass ratio of the sodium chloride-potassium chloride mixed salt system to the phthalocyanine transition metal precursor is 5:1-20:1; In the sodium chloride-potassium chloride mixed salt system, the molar ratio of sodium chloride to potassium chloride is 1:1-3:1; The mixed sample is calcined by a gradient temperature increase method, and the calcination parameters are: heating to 700-1100°C at a heating rate of 3-5°C / min, and then keeping the temperature for 0.5-4h.
2. The method for preparing the salt-assisted synthesis of defect-rich transition metal M-NC porous nanosheet material according to claim 1, characterized in that: In the ethanol-water mixed solution of the phthalocyanine transition metal precursor, the volume ratio of ethanol to water is 1:1-5:
1.
3. The method for preparing the salt-assisted synthesis of defect-rich transition metal M-NC porous nanosheet material according to claim 1, characterized in that: The mass ratio of glucose to urea is 1:1-2:1, and the concentration of glucose and urea in the mixed solution is 10-15 g / L.
4. The method for preparing the salt-assisted synthesis of defect-rich transition metal M-NC porous nanosheet material according to claim 1, characterized in that: The defect-rich transition metal nitrogen-doped carbon porous nanosheet material obtained in step (2) is sequentially acid-washed. In the acidic process, the acid used is hydrochloric acid, nitric acid or sulfuric acid, and the concentration of the acid used is 0.5-2 mol / L.
5. A salt-assisted synthesis of defect-rich transition metal M-NC porous nanosheet material prepared by the method for preparing the salt-assisted synthesis of defect-rich transition metal M-NC porous nanosheet material according to any one of claims 1 to 4.
6. The use of the salt-assisted synthesis of defect-rich transition metal M-NC porous nanosheet material in electrocatalysis of CO2 according to claim 5, characterized in that: The salt-assisted synthesized defect-rich transition metal nitrogen-doped carbon porous nanosheet material was uniformly dispersed in the perfluorosulfonic acid resin Nafion solution as a catalyst and placed on a carbon paper support as a working electrode. It formed a three-electrode system with an Ag / AgCl reference electrode and a platinum column counter electrode for electrocatalytic CO2 reduction.
Citation Information
Patent Citations
Silver-based carbon dioxide reduction catalyst and preparation method thereof
CN111672505A
Preparation of manganese phthalocyanine modified oxhorn-shaped carbon-based catalyst and CO2 electric reduction method
CN111715297A
Preparation method of transition metal-N-C material with two-dimensional nanosheet structure and application of transition metal-N-C material to lithium-sulfur battery
CN112007680A